Impact of Glucose to Mitigate the Heat Stress in Broiler Chickens - Ali, Qasim; Farooq, Umar; Akhtar, Pervez; Khalid, Muhammad Farooq; Khan, Sami Ullah (PSM Biological Research, 2019)
Over a few decades, the main purpose of the progress in the poultry genes is to obtain optimum production at maximum temperature. However, these days the increase in the tremendous heat waves and the increased sensitivity of poultry genomes to the heat stress makes them more alarming to the economic poultry losses. So, the main objective of this article is to assess the importance of glucose utilized in drinking water to mitigate the bad impacts of heat stress in poultry. Though, in the latest changing environmental conditions, it is very imperative to use glucose against heat stress that is advantageous in the response to the changing environment.